Rapid conductometric sensor for the analysis of cyanide using imidazole based receptor - Paul, Anirban; Perween, Mosarrat; Saha, Sukdeb; Srivastava, Divesh N.; Das, Amitava (Physical Chemistry Chemical Physics, 2015)
A specific and efficient hydrogen bonding interaction between cyanide and the HN-H [imidazole] in an aqueous medium has been utilized for the selective recognition of cyanide under physiological conditions. The possibility of utilizing such an interaction for developing any practical device for the specific detection of cyanide in an aqueous environment has not been explored to date. We now report a simple dip and read conductometric sensor for cyanide ions using a tailored electrode in aqueous media. The purpose built reagent, 2-phenyl-1H-anthra-[2,3-d]-immidazole-5,10 dione was immobilized in a polyaniline matrix to fabricate this conductometric device. The homogeneous immobilization of the receptor in polyaniline was confirmed by FT-IR mapping. The proposed transduction mechanism is charge neutralization on the polyaniline moiety, which ultimately inhibits the protonation resulting in a decrease in the conductance of polyaniline. The sensor response was measured in three ranges of cyanide concentration (10(-10) M to 10(-8) M; 10(-8) M to 10(-6) M and 10(-6) M to 10(-3) M). Whereas the device is found insensitive in the first range, it acts as a detector in the second range and as a proportional sensor in the third range. The minimum detection limit of this device was found to be 10 nmol L-1 (2.6 ppt), which is significantly less than the WHO guideline values. The responses have been investigated under various conditions such as different pH and the electrochemical state of the polymer. The current device has been found to be better close to neutral pH and at a 400 mV vs. Ag/AgCl potential. The reproducibility and repeatability of the sensor was investigated and interference studies were performed.